FLEXING: SHOWING OFF ON EMOTION-DRIVEN X COMMUNITIES OF MARAH-MARAH AND RAMAH-RAMAH - Maura Maulidya Asyhari; Nabiilah Maheswari; Alfrida Riska Wardani; Aniisa Dhiyaa Afifah; Yusrika Safitri; Muhammad Fauzan Azis (Universitas Warmadewa, 2025)
This study aims to explore the practice of showing off, which is highlighting wealth, achievements, or lifestyle in the context of emotions conveyed through the “Marah-Marah” and “Ramah-Ramah” communities on the X social media platform. This research method uses descriptive qualitative data sources from both communities containing posts that describe showing off behavior and are driven by emotion. Data collection was done by observing interactions in the community and including supporting data, namely textual and visual. The results showed that different emotions between the two communities drove the explicit showing-off behavior performed by X users. In the Marah-Marah community, showing off is shown by mentioning luxury items with an emotional tone while in the Ramah-Ramah community showing off is shown by an achievement or one's ability towards something. This study concludes that showing off appears in both negative and positive contexts.